2016
DOI: 10.18632/oncotarget.7992
|View full text |Cite
|
Sign up to set email alerts
|

Loss of SOCS3 in myeloid cells prolongs survival in a syngeneic model of glioma

Abstract: In glioma, microglia and macrophages are the largest population of tumor-infiltrating cells, referred to as glioma associated macrophages (GAMs). Herein, we sought to determine the role of Suppressor of Cytokine Signaling 3 (SOCS3), a negative regulator of Signal Transducer and Activator of Transcription 3 (STAT3), in GAM functionality in glioma. We utilized a conditional model in which SOCS3 deletion is restricted to the myeloid cell population. We found that SOCS3-deficient bone marrow-derived macrophages di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 47 publications
0
31
1
Order By: Relevance
“…Furthermore, Deng et al (21) reported the development of spontaneous colon tumors in the Csf1r-iCre model, suggesting that STAT3 deletion in myeloid cells enhances tumorigenesis, which is consistent with our findings in the mammary tumor models. Additionally, LysM-Cre-mediated deletion of SOCS3, a negative regulator of STAT3 activity, led to increased STAT3 activation in macrophages, reduced tumor growth, and increased survival in a mouse model of glioma (62). Finally, studies of myeloid STAT3 in the context of viral infection have demonstrated impaired activation of T cells and NK cells (63), suggesting that STAT3 regulation of myeloid cells is highly context-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Deng et al (21) reported the development of spontaneous colon tumors in the Csf1r-iCre model, suggesting that STAT3 deletion in myeloid cells enhances tumorigenesis, which is consistent with our findings in the mammary tumor models. Additionally, LysM-Cre-mediated deletion of SOCS3, a negative regulator of STAT3 activity, led to increased STAT3 activation in macrophages, reduced tumor growth, and increased survival in a mouse model of glioma (62). Finally, studies of myeloid STAT3 in the context of viral infection have demonstrated impaired activation of T cells and NK cells (63), suggesting that STAT3 regulation of myeloid cells is highly context-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…SOCS3 protein is commonly known to serve as a negative regulator of STAT3, which is the key physiological regulator in immune homeostasis and diseases pathogenesis [ 89 91 ]. SOCS3 has been shown to be induced by a wide variety of the cytokines and growth factors, such as IL-1β, 2, 4 and M-CSF [ 92 , 93 ].…”
Section: Socs Proteins Family and Macrophage Polarizationmentioning
confidence: 99%
“…In this model, decreased infiltration of gliomas by M2 polarized macrophages occurred. This loss of SOCS3 in myeloid cells was associated with an increased infiltration of the tumors by M1 macrophages and CD8+cytotoxic T cells with a concomitant decrease in infiltrating Treg cells [9]. This same group had previously shown that SOCS3 deficiency enhanced M1 polarization and inflammation and conversely, that Polarized myeloid cell phenotypes and associated SOCS1-SOCS3 proteins play key roles in inflammation as well as in immune regulation.…”
Section: Editorialmentioning
confidence: 76%